P3HB from CH4 using methanotrophs: aspects of bioreactor, fermentation process and modelling for cost-effective biopolymer production - Safaeian, Parya; Yazdian, Fatemeh; Khosravi-Darani, Kianoush; Rashedi, Hamid; Lackner, Maximilian (Frontiers in Bioengineering and Biotechnology, 2023)
P3HB (poly-β-hydroxybutyrate), an energy-storage compound of several microorganisms, can be used as bioplastics material. P3HB is completely biodegradable under aerobic and aerobic conditions, also in the marine environment. The intracellular agglomeration of P3HB was examined employing a methanotrophic consortium. Supplanting fossil, non-degradable polymers by P3HB can significantly reduce the environmental impact of plastics. Utilizing inexpensive carbon sources like CH4 (natural gas, biogas) is a fundamental methodology to make P3HB production less costly, and to avoid the use of primary agricultural products such as sugar or starch. Biomass growth in polyhydroxyalkanoates (PHA) in general and in Poly (3-hydroxybutyrate) manufacture in specific could be a foremost point, so here the authors focus on natural gas as a proper carbon source and on the selection of bioreactors to produceP3HB, and in future further PHA, from that substrate. CH4 can also be obtained from biomass, e.g., biogas, syngas methanation or power-to-gas (synthetic natural gas, SNG). Simulation software can be utilized for examination, optimizing and scale-up of the process as shown in this paper. The fermentation systems continuously stirred tank reactor (CSTR), forced-liquid vertical loop bioreactor (VTLB), forced-liquid horizontal tubular loop bioreactor (HTLB), airlift (AL) fermenter and bubble column (BC) fermenter were compared for their methane conversion, kLa value, productivity, advantages and disadvantages. Methane is compared to methanol and other feedstocks. It was discovered that under optimum processing circumstances and using Methylocystis hirsuta, the cells accumulated 51.6% cell dry mass of P3HB in the VTLB setup.